Pelatihan dan Pendampingan Akuntansi Computer dan Aplikasi Perkantoran dengan Menggunakan Microsoft Excel untuk Meningkatkan Capability Himpunan Wanita Disabilitas (HWDI) Kabupaten Lombok Barat - Khalid Abjadi; Titiek Herwanti; Endar Pituringsih (Jurnal Gema Ngabdi, 2021)
Disabled empowerment is a process in which people with disabilities are given knowledge and skills training to live independently. The purpose of this activity is to improve the ability and skills of managers and members of HWDI in West Lombok Regency. The activity is carried out by holding training and assistance in computer accounting and office accounting using Microsoft Excel, the results of the implementation of this activity are expected to improve the capabilities of managers and members of HWDI. In addition, this training and assistance is carried out to provide new abilities and skills to managers and members of HWDI, so they can take advantage of digitalization opportunities to improve the economy of people with disabilities. This training and mentoring activity will be aimed at managers and members of HWDI in West Lombok Regency. The implementation of the activities is carried out with an approach to providing material and mentoring computer accounting training and office accounting using Microsoft Excel. The results of counseling and training activities on computer accounting and office accounting in increasing the knowledge and capability of the management and members of the West Lombok Regency HWDI are useful and supported by the management and members, so that in the future they can remain independent.